Comment on “Acupuncture and Moxibustion in the Treatment of Gynecological Perioperative Anxiety: A Systematic Review and Meta-Analysis” [Letter] - Lin B; Zhang F (Journal of Pain Research)
Bo Lin,1 Fan Zhang2 1Department of Nursing, Xiangyang Hospital of Traditional Chinese Medicine, Xiangyang, Hubei, People’s Republic of China; 2Department of Nephrology A, Longhua Hospital Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Fan Zhang, Department of Nephrology A, Longhua Hospital Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China, Email fan_zhang1993@163.com